Entretenimiento en entorno virtual de una central de generación híbrida. - Chiluisa Saragosin, Max Gonzalo (2018)
This article describes a Virtual Environments application of a Hybrid Power Plant, for professionals in Electrical Power Systems training. The application is developed in the Game Engine Unity 3D and features three different modes as: immersion, interaction and failure modes, which enhance professional’s skills through visualization of the plant components and different processes operation. Additionally, failure mode is proposed, it simulates wrong maneuvers consequences and effects. The Generation Environment is integrated by wind turbines and photovoltaic panels that interact through a mathematical model and enables manipulation of dependent variables bringing out a more realistic background.